Rate and amount of abandoned, lost and discarded gear from the Iranian Persian Gulf Gargoor pot fishery. (July 2022) - Haghighatjou, N.; Gorgin, S.; Ghorbani, R.; Gilman, E.; Naderi, R.A.; Raeisi, H.; Farrukhbin, Sh
Abstract: Derelict fishing gear causes substantial adverse ecological and socioeconomic impacts. This study determined the rate of production of derelict gear from an Iranian Persian Gulf fishery using a type of fishing pot regionally known as gargoor. From November 2018 to July 2020, fishermen were surveyed and pots were marked in Jofreh, Jalali and Ganaveh, which are three major areas of Iran's coastal waters. We tagged 1, 565 pots from 15 fishing vessels, which were then monitored throughout the study period, and surveyed 240 fishermen. Only 1% of tagged pots were retrieved, with 43% having been lost and 56% abandoned or discarded. Similarly, surveyed fishermen estimated losing 20% and abandoning or discarding 76% of pots, retrieving only 4%. Fishermen from the three study areas were estimated to annually produce over 287, 000 derelict pots. Main causes of the production of abandoned, lost and discarded fishing gear were: (1) gear conflicts with shrimp trawls, anchored gillnets and strings of pots; (2) inclement weather; (3) strong currents; and (4) at the end of fishing season, abandonment and discarding of end-of-life pots. Potential solutions to the abandonment and discarding of pots at the end of fishing seasons, which was the largest source of derelict gear production in this fishery, include: increased awareness by fishermen of the adverse effects of derelict pots, development of more durable gear components that enable pots to last for multiple seasons, and detection and removal of derelict pots. Potential solutions to gear loss include: zoning to spatially and temporarily separate fisheries with gear conflicts, improved communication between vessels to avoid gear conflicts, training for new entrants, gear marking to enhance pot gear visibility in areas where theft is a low risk, and avoidance of fishing during inclement weather. These findings of extremely high rates of derelict gear production from Iranian pot fisheries in the Persian Gulf and identification of causes for abandonment, loss and discarding of fishing gear highlight the urgent need to introduce relevant mitigation interventions. Highlights: Main causes were identified for derelict gear production in a Persian Gulf pot fishery. Rates and magnitude of abandoned, lost and discarded pots were estimated. Mitigation methods relevant to identified causes of derelict gear production are proposed.